Yemen Arab Republic : diversifying the industrial base - United Nations Industrial Development Organization (New York : United Nations Industrial Development Organization, 1989)
This is a review on industrial development of Yemen prepared by the regional and country studies.
Includes bibliographical references: p.164-166.
oo 11/04/2019
Loans
Keywords: Manufactures; Economic history; Industrial policy; Industrial promotion; Industries